2004
DOI: 10.1097/00001813-200404000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of human topoisomerase IIα correlates with altered expression of transcriptional regulators NF-YA and Sp1

Abstract: Topoisomerase IIalpha (Topo IIalpha) is an essential nuclear enzyme with a role in the maintenance of DNA topology. Topo IIalpha is a target for several anticancer drugs and the levels of activity of this enzyme have been implicated in the development of drug resistance. Our objective was to identify regulatory transcription factors involved in drug-induced down-regulation of Topo IIalpha. A breast cancer cell line was subjected to a pulsed exposure of doxorubicin and resistant clones propagated. Whole-cell ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…We have previously shown that Sp1 can up-regulate transcription of topoisomerase IIα [9,18] and this current study supports Sp1 as a transcriptional activator of topoisomerase IIα. These findings are consistent with other work, which has shown that in the rat topoisomerase IIα promoter, Sp1 is a transcriptional activator at the GC2 element, which is spatially equivalent to the GC1 element of the human topoisomerase IIα promoter [23].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have previously shown that Sp1 can up-regulate transcription of topoisomerase IIα [9,18] and this current study supports Sp1 as a transcriptional activator of topoisomerase IIα. These findings are consistent with other work, which has shown that in the rat topoisomerase IIα promoter, Sp1 is a transcriptional activator at the GC2 element, which is spatially equivalent to the GC1 element of the human topoisomerase IIα promoter [23].…”
Section: Discussionsupporting
confidence: 86%
“…The effects of Sp1 and Sp3 on transcription were tested by co-transfecting increasing amounts of Sp1 and Sp3 expression vectors respectively (Figure 3). Sp1 has been shown previously to be a transcriptional activator in both HeLa [9] and MDA MB 231 [18]. Figure 3 clearly shows Sp3 acts as a transcriptional repressor of human topoisomerase IIα by decreasing expression in a dose-dependent manner by approximately 60% at the highest concentration used.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…TOP2A is an essential nuclear enzyme with a role in the maintenance of DNA topology and reportedly a target for several anticancer drugs including doxorubicin (18 -22). Decreased expression of TOP2A has been observed in a variety of cell lines that were resistant to a range of chemotherapeutic drugs (18,19,22). TOP2A-targeting anticancer drugs stabilize the TOP2A-DNA cleavable complex, prevent annealing of DNA strands, and cause subsequent double-stranded DNA breakage that leads to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that BM-cyclin 1 could effectively reverse drug resistance in C-A120 cells. With respect to the Topo II poisons, the level or activity of the Topo IIa enzyme can determine the amount of druginduced DNA damage that occurs and in turn might determine the cytotoxicity of the treatment [2]. In addition to the classical MDR, which is due to the overexpression of the MDR transporter (e.g.…”
Section: Discussionmentioning
confidence: 99%